Analyses of the Structure of Lumber Using Ultrasonic Waves - Sidorenko, Irina G.; Durukan, Yasemin; Teplyakova, Aleksandra V. (IEEE NW Russia Young Researchers in Electrical and Electronic Engineering Conference, 2022)
A mathematical model of the acoustic path of the shadow method of sounding wood is proposed. The effective wave propagation speed along the annual layers is determined. The angle of deflection of ultrasound when passing through a finely layered medium is experimentally determined and the parameters of the transducer for reliable ultrasound testing are determined.